Conjunctivitis in patients with atopic dermatitis treated with dupilumab - Ferreira, Sandra (2020)
Atopic dermatitis (AD) is a common, chronic, inflammatory skin disorder with high physical and emotional burden. Robust evidence suggests that interleukin (IL)-4 and IL-13 are key cytokines in the immunopathogenesis of AD. New emerging agents include dupilumab, a fully human monoclonal antibody directed against the IL-4 receptor a subunit that blocks both IL-4 and IL-13 signaling and has shown significant efficacy in patients with moderate-to-severe AD. Dupilumab is approved for the treatment of moderate-to-severe AD, moderate-to-severe eosinophilic or oral corticosteroid-dependent asthma, and chronic rhinosinusitis with nasal polyps. Data from phase phase 2 and 3 studies have revealed that dupilumab generally has a low rate of adverse events, although an increased incidence of mild-to-moderate conjunctivitis has been reported for dupilumab compared with placebo. The present paper reviews the data of dupilumab-associated conjunctivitis and risk factors in adults with moderate-to-severe AD and other atopic diseases in dupilumab clinical trials and addresses the characteristics and treatment options available for this clinically highly relevant condition. Additionally, it presents data from ten studies in the real-life setting with dupilumab. Dupilumab-associated conjunctivitis incidence is higher in AD, although most cases are mild-to-moderate and have good response to topical treatment, with no need to suspend dupilumab therapy